FIELD EFFICACY OF FUNGICIDES AGAINST NECK BLAST OF RICE CAUSED BY CAVARA PYRICULARIA ORYZAE (Journal of Plant Disease Sciences, 2026)
Rice blast, caused by Pyricularia oryzae Cavara, is one of the most important fungal diseases of rice. Among the different phases of blast disease, neck blast is the most destructive and can cause grain yield losses ranging from 1.8% to 37.5%. The present investigation evaluated the efficacy of nine fungicides against neck blast under field conditions at the Agricultural Research Station, Nellore, during three consecutive crop seasons (2020–21 to 2022–23). The experiment was conducted in a randomized block design. The fungicides tested were tebuconazole 25.9% EC @ 1.5 ml L⁻¹, kresoxim-methyl 44.3% SC @ 1.0 ml L⁻¹, pyraclostrobin 100 g L⁻¹ CS @ 2.0 ml L⁻¹, picoxystrobin 22.52% SC @ 1.2 ml L⁻¹, kasugamycin 5% + copper oxychloride (COC) 45% WP @ 1.87 g L⁻¹, kresoxim-methyl 40% + hexaconazole 8% WG @ 1.0 ml L⁻¹, tebuconazole 50% + trifloxystrobin 25% WG @ 0.4 g L⁻¹, azoxystrobin 18.2% + difenoconazole 11.4% SC @ 1.0 ml L⁻¹, and isoprothiolane 40% EC @ 1.5 ml L⁻¹. Pooled analysis of three years' data revealed that tebuconazole 50% + trifloxystrobin 25% WG @ 0.4 g L⁻¹ was the most effective treatment, recording the highest reduction in neck blast incidence (77.73%). Therefore, this fungicide combination is recommended for effective management of rice neck blast under field conditions.
Keywords: Efficacy; Fungicides; Neck blast; Rice; Pyricularia